Methodical approaches on creation of winter rye population varieties for different goal directions - E. I. Utkina; A. V. Voylokov; L. I. Kedrova; N. V. Chugunova (Аграрная наука Евро-Северо-Востока)
The breeding scheme is designed for improvement and differentiation of short-stem rye population varieties for obtaining progenies of different goal directions. The scheme includes testing and selection of inbred progenies originated from self-pollination of annually produced backcrosses. The source of the self-fertility is a line of long-stem genotype carrying mutation of self-fertility marked with isozyme locus. The best in vegetative traits short-stem plants of the initial population are involved in direct and back crosses. The selection is carried out among the inbred progenies constant for the traits determining productivity, lodging and diseases resistance, and goal direction in successive generations of backcrosses. A cross pollination of pre-selected plants heterozygous on self-fertility is carried out at accumulation of progenies having characteristics which meet requirements for selection of forming varieties. In the obtained offspring self-incompatible plants are selected by marker. Cross-pollination of these offspring permits to get heterotic sub-populations constant for short-stem, differentiated for quality, characterized by ecological plasticity and improved performance of resistance and productivity. Simultaneously self-fertile analogs of open-pollinated sub-populations are created in which concentration of genes responsible for selected traits is increased owing to selection as well as in initial sub-populations. These analogs could be used at repeated cycles of selection and as initial material for breeding of hybrid varieties. For test of efficiency of the scheme the analysis of biochemical characters determining grain quality is carried out in 122 inbred progenies produced on the basis of variety Snezhana. Seventeen genotypes are selected having increased protein content, 20 - having highest starch content, 14 - having highest content of soluble pentosans among all nursery, and 18 - having lowest content of soluble pentosans. The part of progenies combines the characters meeting requirements of breeding for baking and forage.